Educational Opportunity Fund Program and Community College Student Retention. (November 2019) - Watson, Aretha; Chen, Rong
Although the existence of state-funded student support services programs dates to the 1960s, studies on how such programs play a role in student success are scarce. By utilizing unique institutional data and a comprehensive conceptual model integrating multiple theories, this study examines the relationship between the New Jersey educational opportunity fund program and first-semester retention at a community college. Results reveal that educational opportunity fund has a positive effect on student retention, and the effect is consistent across different student subgroups. This study provides empirical evidence for greater government commitment needed to fully fund student support services for historically underserved students in community colleges. Future research is suggested to offer additional insight into the effect of government-funded student support services programs on college student retention.